WITHDRAWN: More Severe Hypercoagulable State in Acute COVID-19 Pneumonia as Compared to Other Oneumonia - Spiezia, Luca; Campello, Elena; Cola, Marco; Poletto, Francesco; Cerruti, Lorenzo; Poretto, Anna; Simion, Chiara; Cattelan, Annamaria; Vettor, Roberto; Simioni, Paolo (Mayo Clinic proceedings. Innovations, quality & outcomes, 2021)
The Publisher regrets that this article is an accidental duplication of an article that has already been published, http://doi.org/10.1016/j.mayocpiqo.2020.09.002. The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal